From Language Portraits to Language-In-Education Policies in Higher Education for the 21st Century - Susan Coetzee-Van Rooy (PraxisForschungLehrer*innenBildung, 2023)
The focus of this paper is to contribute to the conversation about 21st century teaching skills from the vantage point of appropriate language-in-education policies for this context that keep the development of 21st century skills in mind. The approach taken was to use language portrait data gathered among students at the North-West University (NWU) in South Africa to establish the nature of their language repertoires and to investigate the relationships between the languages in the repertoire of the participants and 21st century skills. The findings from these analyses were then used to capture recommendations for appropriate 21st century language-in-education policies. The main findings from the analyses are that the participants display multilingual profiles, and that the languages included in the repertoires of the participants perform different functions. The analysis approach towards the language portraits seems to hold great potential to link the information provided in language portraits more directly to language-in-education policies.